2015
DOI: 10.1002/chem.201503479
|View full text |Cite
|
Sign up to set email alerts
|

Trinuclear Cage‐Like ZnII Macrocyclic Complexes: Enantiomeric Recognition and Gas Adsorption Properties

Abstract: Three zinc(II) ions in combination with two units of enantiopure [3+3] triphenolic Schiff-base macrocycles 1, 2, 3, or 4 form cage-like chiral complexes. The formation of these complexes is accompanied by the enantioselective self-recognition of chiral macrocyclic units. The X-ray crystal structures of these trinuclear complexes show hollow metal-organic molecules. In some crystal forms, these barrel-shaped complexes are arranged in a window-to-window fashion, which results in the formation of 1D channels and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 125 publications
3
55
0
Order By: Relevance
“…These results are similar to what has been observed with other metallosupramolecular cage materials. A discrete metallosupramolecular system reported by Yaghi and co‐workers bound 0.8 mol CO 2 per mol Cu I , while the metallomacrocycle of Lisowski and co‐workers encapsulated 1.4 mol per CO 2 per mol Zn II (273 K, 1 bar) . Very recently a tube‐like metallosupramolecular system from Donnelly and co‐workers was found to uptake 0.2 mol CO 2 per mol Zn II ion of the architecture (298 K, 1 bar)…”
Section: Gas Adsorption Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are similar to what has been observed with other metallosupramolecular cage materials. A discrete metallosupramolecular system reported by Yaghi and co‐workers bound 0.8 mol CO 2 per mol Cu I , while the metallomacrocycle of Lisowski and co‐workers encapsulated 1.4 mol per CO 2 per mol Zn II (273 K, 1 bar) . Very recently a tube‐like metallosupramolecular system from Donnelly and co‐workers was found to uptake 0.2 mol CO 2 per mol Zn II ion of the architecture (298 K, 1 bar)…”
Section: Gas Adsorption Studiesmentioning
confidence: 99%
“…In addition to solution studies of gas binding within metallosupramolecular assemblies there has been increasing interest in the solid‐state gas adsorption properties of discrete metallocages. Maverick and co‐workers, have shown that discrete copper(II)‐containing molecular squares will bind H 2 gas in the solid state, while the groups of Yaghi, Batten, and Lisowski have examined the interaction of H 2 , N 2 , and CO 2 with discrete metallocages.…”
Section: Introductionmentioning
confidence: 99%
“…Highly symmetrical, large‐ring poly‐aza chiral macrocycles are of considerable interest because of their applications as molecular building blocks, catalysts, gelators, and discriminating agents . The synthetic method providing such compounds relies on thermodynamically driven cycloimination of dialdehydes with vicinal diamines of the trans ‐1,2‐diaminocyclohexane or threo ‐1,2‐diphenyl‐1,2‐diaminoethane type .…”
Section: Introductionmentioning
confidence: 99%
“…The DCC‐based reversible cycloimination reaction emerges now as a convenient template‐free method providing shape‐persistent, optically pure polyimine macrocycles from structurally predisposed substrates . These polyazamacrocycles are further applied as chiral catalysts and ligands in stereoselective synthesis, as molecular receptors, or as organic porous materials . The use of racemic substrates in cycloimination reactions often provides complex mixtures of diastereoisomers.…”
Section: Methodsmentioning
confidence: 99%
“…[3] These polyazamacrocycles are further applied as chiral catalystsa nd ligands in stereoselectives ynthesis, as molecular receptors, or as organic porousm aterials. [4,5] The use of racemic substrates in cycloimination reactions often provides complex mixtures of diastereoisomers. Chiral self-sorting is achieved in those DCC-based reactions for which the products significantly differ in symmetry and hence in rotationale ntropy.…”
mentioning
confidence: 99%